1974
DOI: 10.3758/bf03333012
|View full text |Cite
|
Sign up to set email alerts
|

The acquisition of a Pavlovian conditioned response in septally damaged rabbits: Role of a competing response

Abstract: Enhanced acquisition of a classically conditioned eyelid response was found following septal injury in rabbits. Eye-opening behavior was four times more frequent in the control Ss. This suggests that faster acquisition is a function of fewer competing responses which might interfere with elaboration of the conditioned response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

1976
1976
2003
2003

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 18 publications
0
0
2
Order By: Relevance
“…The observed increase in emotionality after sep tal lesions in the rabbit stands in apparent contrast to two recent reports [Maser et al, 1974;Lockhart and M oore, 1975] in which septal lesions were also produced in rabbits and no changes in emotionality were re ported. Differences in lesion size probably best account for the discrepan cies between the results of these two studies and the results of the present study.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The observed increase in emotionality after sep tal lesions in the rabbit stands in apparent contrast to two recent reports [Maser et al, 1974;Lockhart and M oore, 1975] in which septal lesions were also produced in rabbits and no changes in emotionality were re ported. Differences in lesion size probably best account for the discrepan cies between the results of these two studies and the results of the present study.…”
Section: Discussioncontrasting
confidence: 53%
“…Differences in lesion size probably best account for the discrepan cies between the results of these two studies and the results of the present study. In neither the study of Maser et al [1974] nor that of L ockhart and Moore [1975] did the presentation of the histology indicate any sub stantial damage to the lateral septal nucleus, whereas this area was exten sively damaged in the present study. In the rat Clody and Carlton [1969] have found that lesions in the septal area which spare the lateral septal nucleus do not produce the 'septal syndrome', and this observation would seem to be valid for the rabbit as well.…”
Section: Discussioncontrasting
confidence: 52%